Neutron Damage in the Plasma Chamber First Wall of the GCFTR-2 Fusion-Fission Hybrid Reactor. (July 2015) - Pinto, L N; Gonnelli, E; Rossi, P C R; Carluccio, T; dos Santos, A
Abstract: The successful development of energy-conversion machines based on either nuclear fission or fusion is completely dependent on the behaviour of the engineering materials used to construct the fuel containment and primary heat extraction systems. Such materials must be designed in order to maintain their structural integrity and dimensional stability in an environment involving high temperatures and heat fluxes, corrosive media, high stresses and intense neutron fluxes. However, despite the various others damage issues, such as the effects of plasma radiation and particle flux, the neutron flux is sufficiently energetic to displace atoms from their crystalline lattice sites. It is clear that the understanding of the neutron damage is essential for the development and safe operation of nuclear systems. Considering this context, the work presents a study of neutron damage in the Gas Cooled Fast Transmutation Reactor (GCFTR-2) driven by a Tokamak D-T fusion neutron source of 14.03 MeV. The theoretical analysis was performed by MCNP-5 and the ENDF/B-VII.1 neutron data library. A brief discussion about the determination of the radiation damage is presented, along with an analysis of the total neutron energy deposition in seven points through the material of the plasma source wall (PSW), in which was considered the HT-9 steel. The neutron flux was subdivided into three energy groups and their behaviour through the material was also examined.